State of Knowledge on Beekeeping Practices in Côte d’Ivoire in the Face of Challenges and Opportunities in the Context of Climate Change - Ouattara, Salimata; Assi-Kaudjhis, Chimène; Adjonou, Kossi; Kouamé, Koffi Félix; Koudegnan, Comlan Mawussi; Kokou, Kouami (European Scientific Journal, ESJ, 2023)
Beekeeping plays an important role in socio-economic development and environmental conservation. This sector is developing in Côte d’Ivoire even if it is an ancient practice. Based on available scientific data, this study aims to take stock of the Ivorian beekeeping sector and its melliferous potential. The aim is to gain a better understanding of the difficulties faced by this sector and to contribute to its sustainable development in the current context of climate change. Côte d’Ivoire’s honey is of good quality and very rich in nutrients: pollen grains, minerals, etc. A part Apis mellifera, other species of bees are present and could be used in keeping. Despite favorable climatic and floristic conditions, beekeeping in Côte d’Ivoire is still in its infancy caused by several challenges: Environmental conditions, lack of training of beekeepers, and weak commitment of stakeholders. To modernize the sector, we need to combine the efforts of the authorities, take into account the recommendations of scientific publications, and encourage the population to understand the importance of preserving plants and bees by practicing modern beekeeping.